The magic school bus. All about earth [videorecording (DVD)]. - Cole, Joanna; Degen, Bruce; Tomlin, Lily; Warner, Malcolm-Jamal; DeSanto, Daniel, 1980- (Scholastic Entertainment : distributed by New Video Group, 2013)
Contains 4 episodes that follow Ms. Frizzle and her class on their science adventures aboard the magic school bus.